Percentile curves for Brazilian children evaluated with the Bruininks-Oseretsky Test of Motor Proficiency, 2nd edition - Luciana Ferreira; José Luiz Lopes Vieira; Francielli Ferreira da Rocha; Pâmela Norraila da Silva; Francielle Cheuczuk; Priscila Caçola; Raquel Nichele de Chaves (Revista Brasileira de Cineantropometria e Desempenho Humano)
This study aimed to (1) create percentile curves and norms for the eight subtests of the Bruininks-Oseretsky Test of Motor Proficiency, 2nd edition (BOT-2) for 6- to 10-year-old Brazilian children and to (2) compare them to the values of the original test manual. To that, we tested a sample of 931 Brazilian children (477 girls, 454 boys) with ages between 6 to 10 with the BOT-2 assessment. The LMS method was used to generate the percentile curves and normative values, with the LMSchartmaker Pro software version 2.54. Results demonstrate that girls had significantly higher scores for the fine motor precision, fine motor integration, manual dexterity and balance subtests, while boys had significantly higher scores on upper-limb coordination, running speed and agility, and the strength subtests. The findings also indicated higher values for the Brazilian group in the subtests of bilateral coordination, running speed and agility, balance, and upper-limb coordination when compared to the North American normative sample. The percentile curves illustrate the increase in motor proficiency levels as age increases, with different trajectories for each subtest. Future studies should continue the investigation of cultural norms and appropriate assessments for the Brazilian population. Here, the creation of percentile curves and norms that are better suited for the Brazilian population can significantly help with assessment and intervention for motor development in distinct settings and with typical and atypical school-age children.